The effect of water immersion and UV radiation aging on the shear behavior of woven continuous Fiber/PEI laminates - Ribeiro, B. [UNESP]; Botelho, E. C. [UNESP]; Rezende, M. C. [UNESP]; Costa, M. L. [UNESP] (My University, 2011)
The hygrothermal and UV radiation influences on shear properties and moisture diffusion aging in polyetherimide (PEI) reinforced with continuous fibers were systematically studied in this research, by using ILSS and losipescu shear tests. The moisture weight gain curves of the PEI composites reinforced with glass fiber and carbon fiber were compared in order to determine the interface effect on moisture absorption. Both composites display similar anomalous diffusion behavior; the PEI reinforced with glass fiber presented higher diffusion and water absorption values. The mechanical results Indicate that moisture associated with temperature and UV radiation degrades the shear properties by about 20%, giving evidences of plasticization of PEI matrix.